Crystal structure and atomic vacancy optimized thermoelectric properties in gadolinium selenides - Qin, Feiyu (2021)
Thermoelectric materials enable the mutual energy conversion of waste heat and electricity, critical to relieve global energy crisis. Hightemperature thermoelectric materials are special species due to their high-temperature stability and noticeable energy conversion efficiency. Here, we report a systematic investigation on high-temperature thermoelectric gadolinium selenides, cubic Gd3-xSe4 (x = 0.16, 0.21 and 0.25) and orthorhombic Gd2Se3-y (y = 0.02, 0.06 and 0.08). High energy synchrotron x-ray diffraction and total scattering are used to investigate the crystallographic and local structures. The atomic-scale cluster of Gd vacancy in cubic Gd2.84Se4 is observed by employing the reverse Monte Carlo simulation. For cubic Gd3-xSe4, its carrier concentration is tuned and multiple conduction bands are incorporated by adjusting Gd vacancy. Experimentally, the gradual increase in effective masses is evidently observed in cubic Gd3-xSe4, which is consistent with the density functional theory (DFT) calculation. A reasonable peak zT value of 0.27 is achieved at 850 K for Gd2.84Se4. On the other hand, adjusting Se vacancy enables the optimization of electron concentration for orthorhombic Gd2Se3-y phase. Its low deformation potential (Ξ = 12eV) with single conduction band gives rise to enhanced electron mobility and higher peak zT value of 0.54 at 850 K for Gd2Se2.98. In addition, a higher zT of 1.2 at1200 K is reasonably predicted for Gd2Se2.98 by using quality factor analysis. This work not just presents a systematic crystallographic investigation of gadolinium selenides, but also provides a deep insight into the charge transport and phonon scattering mechanisms. This study facilitates the exploration of more high-temperature thermoelectric materials.